A Literature Review of Human Resource Management in Improving Performance in Health Services - Sita Dewi Mulyawati; Yuliani Setyaningsih; Hanifa Maher Denny (JTP - Jurnal Teknologi Pendidikan, 2024)
Patient safety is a critical concern in healthcare, and the development and maintenance of patient safety culture are influenced by various human resource factors. This literature review aims to investigate the relationship between human resource factors and safety culture in hospital settings. The study uses a comprehensive literature search using PubMed and Science Direct, focusing on studies conducted from 2020 to 2024 with inclusion criteria based on national journals with an appropriate research scope. The review synthesizes existing research to provide valuable insights into the relationship between human resource factors and patient safety culture within the healthcare environment. The preliminary conceptual framework integrates four main factors: communication, leadership, work procedures, and human factors, providing a comprehensive guide to understanding and improving patient safety culture within the healthcare environment. The review concludes that effective communication, strong and committed leadership, clear work procedures, and the crucial role of human factors are key elements in shaping patient safety culture within the healthcare environment. The findings highlight the interconnectedness of these factors and their collective influence on the safety climate within healthcare organizations. This study contributes to the understanding of how human resource management practices can be utilized to enhance patient safety culture and patient outcomes in hospital environments.